A review of the use and utility of industrial network-based open source simulators: functionality, security, and policy viewpoints. (July 2022) - Ani, Uchenna Daniel; Watson, Jeremy McKendrick; Carr, Madeline; Cook, Al; Nurse, Jason RC
Simulation can provide a useful means to understand issues linked to industrial network operations. For transparent, collaborative, cost-effective solutions development, and to attract the broadest interest base, simulation is critical and open source suggested, because it costs less to access, install, and use. This study contributes new insights from security and functionality characteristics metrics to underscore the use and effectiveness of open source simulators. Several open source simulators span applications in communications and wireless sensor networks, industrial control systems, and the Industrial Internet of Things. Some drivers for their use span are as follows: supported license types; programming languages; operating systems platforms; user interface types; documentation and communication types; citations; code commits; and number of contributors. Research in these simulators is built around performance and optimization relative to flexibility, scalability, mobility, and active user support. No single simulator addresses all these conceivable characteristics. In addition to modeling contexts that match real-world scenarios and issues, an effective open source simulator needs to demonstrate credibility, which can be gained partly through actively engaging experts from interdisciplinary teams along with user contributions integrated under tight editorial controls. Government-led policies and regulations are also necessary to support their wider awareness and more productive use for real-world purposes.